Year of consecration of Our Lady of the Rosary Church - Mumbai Archive Project Team (Jio Institute, 2024)
The year of consecration of Our Lady of the Rosary Church on Dockyard Road, Mazagaon, is inscribed on the outer wall. In 1794, this new church was built a few metres away from the old Gloria Church, which till 1794 was the only church in Mazagaon.